دراسـة تحليـليـة للأمطـار في مناطـق مختلفـة مناخيـاً من سـوريـة - جلب, أدهم (Latakia University Journal -Biological Sciences Series, 2019)
أظهرت الدراسة نتائج تفصيلية دقيقة عن واقع الأمطار في أربع مناطق مختلفة مناخياً (رطبة، شبه رطبة، جافة وشديدة الجفاف) من القطر العربي السوري. تم تحديد خطوط اتجاه التغير السنوية للأمطار حسب معادلات الإنحدار البسيط والتي دلت على التناقص في كل من اللاذقية وصافيتا وتدمر وبقيم هي على التوالي (-172.5، -165.5، -13.8 مم) في حين تزايدت أمطار حماه السنوية وبمقدار (+30.66 مم). تركز معظم التناقص المطري في المحطات أثناء فصل الشتاء باستثناء صافيتا التي تناقصت فيها أمطار الربيع أكثر من أمطار الشتاء. يمكّن مخطط النوموغرام السنوي من تحديد كميات الأمطار السنوية في كافة المناطق المناخية السورية وعند تسع مستويات من الوفرة P %. The study shows exact detailed results about happening rainfall in four different climatic regions( humid, subhumid, arid and hyperarid) in Syrian Arab Republic. Yearly trend rainfall lines that are calculated in simple regression equality were decreased values in Lattakia, Safita and Tadmor as (-172.5, -165.5, 13.8mm) respectively, whereas Hama yearly rainfall were increased as (+30,66 mm). Most rainy decrease in stations appeared in winter except Safita which spring rainfall was decreased in large degree from a winter rainfall. Yearly Nomogram design makes possible to determined yearly rainfall quantity in all Syrian climatic regions as well as in nine levels of P % abundance.